Experiences of Female Partners of People Transitioning Gender: A Feminist Interpretive Metasynthesis. Issue 7 (3rd October 2022) - Smith, Aimee; Morgan, G.; Robertson, N.
Abstract: The needs of romantic partners of people transitioning gender remain neglected within academia and gender services. Following a systematic search, nine studies relating to female partners' experiences were subjected to a thematic metasynthesis. Four themes were generated and entitled Changes in sexual relationship; New roles and responsibilities; Identity and belonging; and Transformation and loss Results are considered in relation to the dominance of the gender-affirmation discourse. Limitations of the review and reviewed studies are highlighted. Clinical implications for couples and partners of people transitioning gender are offered.